2018
DOI: 10.15666/aeer/1605_61556167
|View full text |Cite
|
Sign up to set email alerts
|

Tetraconazole Leads to Alterations in Fusarium Graminearum at Different Molecular Levels

Abstract: The alterations in F. graminearum due to tetraconazole (TCZ) have been investigated in this study. The minimum inhibitory concentration (MIC), and inhibitory concentrations 50% and 25% (IC 50 and IC 25 ) were obtained by adding different concentrations of TCZ to potato dextrose agar (PDA). MIC, IC 50 and IC 25 values were detected as 32, 16 and 8 µg/mL TCZ. Epigenetic changes have been evaluated via genomic template stability (GTS) by the RAPD and CRED-RA methods. GTS values were recorded as 86.73% and 85.71% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
(50 reference statements)
3
17
1
Order By: Relevance
“…The epigenetic status of two barley genotypes was decreased. However, in comparison to previous studies, a narrower range of change was detected in this study (Nardemir et al 2015, Gazdağlı et al 2018a, Yörük 2018). According to the findings obtained from this study, it can be concluded that terpinolene does not affect barley's physiology, transcriptomics, epigenetics, and oxidative stress levels.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The epigenetic status of two barley genotypes was decreased. However, in comparison to previous studies, a narrower range of change was detected in this study (Nardemir et al 2015, Gazdağlı et al 2018a, Yörük 2018). According to the findings obtained from this study, it can be concluded that terpinolene does not affect barley's physiology, transcriptomics, epigenetics, and oxidative stress levels.…”
Section: Discussioncontrasting
confidence: 96%
“…Enniatin synthesis related esyn1 gene expression was significantly downregulated due to terpinolene treatment. This result presented similar data with previous studies including deoxynivalenol and fumonisin biosynthesis inhibition (Jurado et al 2008, Yaguchi et al 2009, Gazdağlı et al 2018a, Yörük 2018. In comparison to these investigations, terpinolene had a strong effect on mycotoxin inhibiting activity and, this is the first report to show that terpinolene could inhibit enniatin biosynthesis at transcription level.…”
Section: Discussionsupporting
confidence: 91%
“…In RAPD and CRED-RA analyses, both genomic template stability and epigenetic alterations were detected. A moderate level of alterations in genomic template stability and type I/IV and type II/III methylation profiles were obtained in this study [19,30]. However, alterations on chromosomal regions would increase the effects of camphor on the aggressiveness and viability of F. graminearum and F. culmorum .…”
Section: Discussionmentioning
confidence: 69%
“…The major components of essential oils obtained from plant extracts (kapyrrole derivatives, indole derivatives, etc.) have been used to inhibit fungal growth [17,18,19]. One of the major components of essential oils, camphor (C 10 H 16 O), is a bicyclic monoterpene ketone widely found in several aromatic plants such as Cinnamonum camphora , Piper capense , and Salvia officinalis .…”
Section: Introductionmentioning
confidence: 99%
“…Tetraconazole was previously shown to induce cell death in fungi [45]. We hypothesized that tetraconazole-induced cell death in our model fungi S. pombe was related tothe apoptotic activity of this triazole.…”
Section: A Tetraconazole-induced Cytotoxicity Is Dose-dependentmentioning
confidence: 94%